Wychowanie do harmonii i piękna duchowego w wizji pedagogicznej Edmunda Bojanowskiego - Jasnos, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Today’s world is referred to as „shaky reality”. Increasingly visible liberalism in norms and values leads to the loss of man himself in the world. Also, the perception of beauty has been shaken. Many times within the framework of the justification of lack of aesthetic education there is expressed the view of the freedom of subjective perception – beautiful is what a given person considers as such. The beauty identified in history with good and harmony has ceased to matter. The ugliness of a human being has crept into a certain degree of usurpation of consciousness and consequence in creating norms of life. It is necessary to rediscover the value of upbringing for beauty so that a person can re-discover the harmony and the desire for perfection. This article is an attempt to present a vision of education for the harmony and spiritual beauty of Edmund Bojanowski as a contemporary proposition for modern education.